Integration of airborne geophysics and geology in north-eastern Burkina Faso - N. Bournas; A. Prikhodko (Instituto de Ingenieros de Minas del Peru, 2008)
A new litho-structural map was derived from the airborne geophysical survey and the 3D inversions. The newly identified faulting structures are suggested to have played a key role in the gold mineralization control. Several kimberlite targets, whose magnetic response is similar to known diamantiferous kimberlite pipes occurring within the study area, were identified from the 3D inversion results. Enhanced spectrometric data imaging and their interpretation results helped detect several uranium targets occurring within the Neoproterozoic sediments and the Eburnean pegmatites of the basement rocks.